Implementation critical thinking in teaching Islamic education - Ahmad Dahari, Aminurrashid; Suhid, Asmawati; Mohd Fakhruddin, Fathiyah (Human Resource Management Academic Research Society, 2019)
Critical thinking is a worth skill inculcate pure thought in teaching Islamic Education exclusively to enhance meaningful learning outcomes. These elements of critical thinking need to be integrated into the process of knowledge acquisition by teachers so that students can get deep understanding and make appropriate judgments when dealing with specific situations in life. In this research, an analytical research being used to apply critical thinking framework which built based on the theory and approach of Critical Thinking Models according to Islamic Epistemology. In addition, technology integration and supportive learning environment conducive to providing a practical framework. These results create collaborative interactions that will focus on assessing student achievement in all aspects. Clarification of this thinking framework can provide a more active and effective teaching and learning environment. This critical thinking framework can be applied based on seven steps involved. These include student-centred strategies, discussion methods, questioning and feedback techniques, integration and synthesis of information and coming up with new ideas. This conceptual paper concludes that teaching applies critical thinking can shed light on some of the most profound and meaningful features of teaching. The implications also suggest some additional teachers' basic skills such as conceptual and procedural skills, inquiry, logic and Mantik. All these skills and competencies empowerment the credibility and capacity of teachers whom being consistently in developing high-level thinking skills in 21st century pedagogy.